Endoscopic lung volume reduction: an expert panel recommendation - update 2017 - Herth, Felix (Respiration, 2017)
Interest in endoscopic lung volume reduction (ELVR) technologies for emphysema is consistently growing. In the last couple of months, several endoscopic options (e.g., endo- or intrabronchial valves, coil implants, and thermal vapor ablation) that have been evaluated in randomized controlled trials have been reported with the ultimate goal of improving respiratory mechanics and alleviating chronic dyspnea. Patients presenting with severe air trapping and thoracic hyperinflation have the greatest potential to derive benefit from ELVR procedures. Baseline assessment should ideally include cardiological evaluation, high-resolution computed tomography scan and perfusion scintigraphy, full pulmonary function tests, and cardiopulmonary exercise testing. This expert statement updates best practice recommendations regarding patient selection and utilization of these various techniques for the treatment of patients with advanced emphysema.